Company size, profitability, tangibility, free cash flow, and growth opportunity that affect the capital structure in manufacturing company - Chandra, Ambrosius Fabian (Universitas Tarumanagara, 2017)
The purpose of this research is to find the influence of company size, profitability, structure of assets, free cash flow, and growth opportunity toward capital structure in manufacturing companies that are listed on the Indonesian Stock Exchange. The population of this research is a manufacturing company that was listed on the Indonesian Stock Exchange in the period 2013-2015. The sampling technique used is the purposive sampling method. Multiple regression analysis techniques were used in analyzing the data. The level of significance used to examine the regression is 5%. The results of this research conclude that tangibles, free cash flow, and growth opportunity affect capital structure. Company size and profitability do not affect the capital structure ratio. The result from the f-test indicates that the data used and the regression model fit in this research.